IPTEKS PERHITUNGAN PENYUSUTAN AKTIVA TETAP MENURUT STANDAR AKUNTANSI KEUANGAN PADA PT. MASSINDO SINAR PRATAMA MANADO - Goni, Yuvita M. F; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2018)
Fixed assets are tangible assets acquired in ready to use or built first, used in the company operations, not intended for sale in the framework of the normal activities of the company and has a useful life more than one year. Depreciation is the process of allocation of the acquisition cost into the applicable cost of deductions in calculating profit. Calculation of depreciation fixed assets according to financial accounting standards using five methods: the straight-line method, declining balance method, sum of the years digit method, service hours method, and the unit of productions method. The purpose of this study was determine the application of methods of depreciation fixed assets according to financial accounting standards in PT. Massindo Sinar Pratama Manado. The applied ipteks method is the calculation of depreciation of fixed assets in accordance with financial accounting standards. The result showed the company uses the straight line method and the declining balance method in calculating depreciation of its fixed assets. PT. Massindo Sinar Pratama Manado should not only perform depreciation calculations in accordance with financial accounting standards but also must be in accordance with the provisions of taxation in order not to need to be done fiscal correction.